2017
DOI: 10.1128/aac.02700-16
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycle Thiazole Compounds Exhibit Antifungal Activity through Increase in the Production of Reactive Oxygen Species in the Cryptococcus neoformans-Cryptococcus gattii Species Complex

Abstract: Human cryptococcosis can occur as a primary or opportunistic infection and develops as an acute, subacute, or chronic systemic infection involving different organs of the host. Given the limited therapeutic options and the occasional resistance to fluconazole, there is a need to develop novel drugs for the treatment of cryptococcosis. In this report, we describe promising thiazole compounds 1, 2, 3, and 4 and explore their possible modes of action against Cryptococcus. To this end, we show evidence of interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In contrast, the positive control, Triton X-100, caused hemolysis at all concentrations. These findings are consistent with previous studies showing that thiazoles heterocyclic compounds do not cause damage to mammalian blood cells [20,21].…”
Section: Resultssupporting
confidence: 93%
“…In contrast, the positive control, Triton X-100, caused hemolysis at all concentrations. These findings are consistent with previous studies showing that thiazoles heterocyclic compounds do not cause damage to mammalian blood cells [20,21].…”
Section: Resultssupporting
confidence: 93%
“…Sá et al . [ 27 ] showed evidence that CHT target action is related to interference in antioxidant fungal system and here in this work we show that in addition to this CHT is also capable of inhibiting C. albicans adhesion in HBEC and shows an indication in reducing of biofilms.…”
Section: Resultssupporting
confidence: 66%
“…In a previous work [ 16 ] we had demonstrated that there was no toxicity to mammalian cells, and recently we verified that CHT is nontoxic to human erythrocytes [ 27 ]. These findings indicate that CHT has potential in a murine model, which is considered the gold standard for studying pathogenesis, quantifying virulence, and analyzing the efficacy of antifungal drugs [ 30 ].…”
Section: Discussionmentioning
confidence: 95%
“…On the one hand, the antifungal effects of many compounds were confirmed to be related to the elevated endogenous ROS. Compounds with different scaffolds, such as shikonin, heterocycle thiazole compounds, clerodane type diterpene, and SM21, exhibited antifungal activity through increasing the production of ROS in fungi (Miao et al, 2012;Bhattacharya et al, 2015;de Sa et al, 2017;Truong et al, 2018). On the other hand, the induction of elevated endogenous ROS is the mechanism of many antifungal synergists.…”
Section: Discussionmentioning
confidence: 99%